2015
DOI: 10.1021/acs.orglett.5b01733
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted N-Pyridylation of Heteroarenes Using N-Propargyl Enaminones as Equivalents of Pyridine Scaffolds

Abstract: N-Pyridylation of various N-heteroarenes, including N-heteroarene-containing peptides, was achieved using N-propargyl enaminones (isolated or generated in situ from propargyl amine and propynones) as masked polysubstituted pyridine cores. This metal-free procedure proceeds under mild reaction conditions and generates 1 equiv of H2O as the sole byproduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Although N ‐propargylic β‐enaminones could serve as potential precursors for the synthesis of seven‐membered ring systems such as 1,4‐oxazepines, very few reports have appeared to date. Cheng and Cui have shown that, under strong basic conditions, N ‐propargylic β‐enaminones produced 1,4‐oxazepines in situ, which undergo a series of rearrangements and concomitant reactions with heteroaromatic nitrogen nucleophiles to afford N‐heteroarene‐substituted pyridines (Scheme c) . When the reactions were stopped after a few minutes, the corresponding 1,4‐oxazepine derivatives could be isolated in low to good yields.…”
Section: Introductionmentioning
confidence: 99%
“…Although N ‐propargylic β‐enaminones could serve as potential precursors for the synthesis of seven‐membered ring systems such as 1,4‐oxazepines, very few reports have appeared to date. Cheng and Cui have shown that, under strong basic conditions, N ‐propargylic β‐enaminones produced 1,4‐oxazepines in situ, which undergo a series of rearrangements and concomitant reactions with heteroaromatic nitrogen nucleophiles to afford N‐heteroarene‐substituted pyridines (Scheme c) . When the reactions were stopped after a few minutes, the corresponding 1,4‐oxazepine derivatives could be isolated in low to good yields.…”
Section: Introductionmentioning
confidence: 99%
“…Enaminones combine ambident nucleophilicity of enamine and the ambident electrophilicity of enone to behave as versatile building blocks and synthetic intermediates in heterocycle synthesis . Our group have recently developed some efficient methods for the preparation of heterocycles, such as 1,2,3‐triazoles, pyrroles, pyridines, benzo[ b ][1,4] oxazepines, quinoxalines, N‐( 2‐pyridyl)pyrroles and benzo[ b ][1,4]oxazins based on enaminones under transition metal free conditions. In our continuing efforts in enaminone chemistry, herein we report a novel protocol to 2,4,6‐triarylpyridines from easily accessible N‐ enaminones and chalcones under base conditions (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Recently, Cheng et al developed a simple and efficient methodology for the synthesis of 2-(1-heteroaryl) pyridines 38 by the reaction between 1,3-diphenyl-3-(prop-2-ynylamino)prop-2en-1-one 36 and N-heteroarenes 37 (Scheme 16). 20 NaOH was the most efficient catalyst among the bases such as LiO t Bu, NaO t Bu, K 2 CO 3 , KOH, Et 3 N etc for this reaction. This NaOH- catalyzed reaction is applicable for a diverse set of nitrogen nucleophilic source, such as indole, pyrrole, imidazole, pyrazole, carbazole, and benzimidazole.…”
Section: Pyridinesmentioning
confidence: 97%